Development of High-Order Thinking Skills Assessment Instrument for High School Students on Rotational Dynamics - Musfiroh, Siti; Rosidin, Undang; Viyanti, Viyanti (Jurnal Pembelajaran Fisika, 2023)
This study aimed to develop a test instrument for high school physical reasoning abilities related to rotational dynamics. This study aimed to determine: Quality of the Instrument Quality of the Higher Order Thinking Ability Instrument in senior high school Physics, including content validity of the expert judgment, empirical validity based on item suitability using the Rasch and PCM models, reliability, and item difficulty index; and profile of high school physics advanced reasoning test scores. This research is research and development. The development model used is based on the Borg & Gall development model. The research was conducted at MAN 1 Bandar Lampung with 42 students in class XI. Using the Quest program, reliability was analyzed using the Quest program, which was represented by internal consistency values and item difficulty indexes analyzed using the Quest program. The results of the ability measurement profile are grouped into three categories presented in the analysis of the Quest program assessment. Research and development resulted in a high-quality thinking ability test instrument for high school physics. The results are the quality of the tool's content based on the actual assessment in the valid category. Empirical validity is based on the suitability of the item with the Rasch model IRT approach with highly reliable criteria. Task difficulty varies from -2.17 to 1.51. Generally, the results of measuring high-level thinking skills show that students have medium-level skills.Keywords: Higher Order Thinking Skill, Rotational Dynamics, Rasch Model, Partial Credit ModelDOI: http://dx.doi.org/10.23960/jpf.v11.n2.202302